Effects of heat stress on germination and tube growth of stored pollen in Actinidia eriantha. Issue 2 (2nd April 2016) - Seyrek, UA; Tao, J; Huang, C; Lang, B; Zhong, M; Xie, M; Qu, X; Xu, X
ABSTRACT: Kiwifruit has a high commercial value and is especially rich in vitamin C. Successful fruit set in kiwifruit depends on several reproductive processes including pollen germination and pollen tube growth. In this study, we investigated impacts of heat stress temperatures (27, 30, 33 and 36 °C) on pollen germination and pollen tube growth of 25 wild genotypes of Actinidia eriantha . Before heat stress application, pollens were stored at −20 °C for 6 months. The results showed great variation among genotypes in each treatment. Eight genotypes showed no significant change in the reduction of germination percentage. Some genotypes gave unsteady response in tube growth. MH22, MH30 and MH58 were evaluated as more tolerant genotypes. In contrast, MH48 and MH67 were the two most sensitive genotypes. The research of heat stress impact on pollen germination and pollen tube growth will be helpful for breeding new varieties and the identified tolerant genotypes can be used in future breeding programmes.